Increasing Students Confidence in Learning Characterizations in Arts lessons using The Dramatic Learning Model (PTK in X Science 6 Class, High School 4 Serang City) - Azis, Abdul; Roekmana, Giri Mustika; Rizal, Syamsul (MATRA: Jurnal Seni Musik Tari Teater & Rupa, 2023)
Learning activity is an effort done consciously by man for a process of better changes, from the ones who are unable to be able, and from those who haven’t gotten used to it to got used to it. As a student, we need to have confidence, especially in the learning process, for lack of confidence could be an obstacle not just for the students but also the the educational staff to create a good learning environment. As according to what had been said in the teacher’s ethnicsl code, that teachers should create a greater school environment that highly supports the success of a learning process. The goal of this research is to know the students learning process and to increaser their confidence in those learning process. A classroom action research is the method used for this research by using the Dramatic Learning model an using Spiral Kemmis and Mc. Taggart’s research designed. The result of this research showed a students learning process that have an increase in the active learning process based on a better confidence in the students, the increasing students confidence in the pre cycle showed an average of 24%, cycle 1 showed an average of 39% after three action was done, and cycle 2 showed an average 76% after three actions was done. Based on this research, it can be concluded that learning using the Dramatic Learning model can increase the students confidence.